Everything is interconnected towards a globalization with a human face and an integral ecology - Ogbonnaya, Joseph 1968-; Briola, Lucas (Milwaukee Marquette University Press, 2019)
"This collection of essays serves the calls of Catholic social teaching for a globalization with a human face (Pope John Paul II) and an integral ecology (Pope Francis). Aided by the thought of Bernard Lonergan and Robert Doran, the contributors take an interdisciplinary approach, focusing on questions pertaining to politics, economics, social theory, environmental studies, and theology"--
Includes bibliographical references and index
Keywords: Globalization -- Religious aspects -- Catholic Church; Christian Sociology -- Catholic Church